RECONSTRUCTION LAW OF PUNISHMENT AGAINST CHILDREN NARCOTICS ABUSE-BASED PROGRESSIVE LAW - Salomo Ginting; Darwinsyah Minin (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Children who do not abuse drugs merely as criminals, but as victims. Second, starting from the thought that children who abuse drugs are also victims, efforts to provide protection for children who abuse drugs is also a priority. This study aims to determine the legal construction of the criminal prosecution against perpetrators of child abusers of narcotics, criminal prosecution against perpetrators of child abusers of narcotics, as well as the reconstruction of criminal law against perpetrators of child abusers of narcotic-based progressive law. This study is normative, ie methods that describe or explain a fact systematically later analysis done legally with the linking of the data and facts obtained convictions related to child abusers of narcotics and associated with the legislation. Reconstruction of sentencing child abusers of narcotics with the principle of diversion and restorative justice with due regard to the principle of the best interests of the child that is no crime to children, through the reconstruction of Article 127 paragraph (1) of Law No. 35 of 2009 by adding provisions stated in Article 127 paragraph ( 1) a, b, and c does not apply to child abusers of narcotics, and every child abusers of narcotics required to undergo medical rehabilitation. it can realize the decision imposing the rehabilitation of child abusers of narcotics as a punishment-based progressive law in realizing the restorative justice. Law enforcement officials must work together and build a shared perception of the protection against child abusers of narcotics. The concept of diversion and restorative justice are two concepts which aims to find an alternative solution to the child offender drug abuse. The concept of diversion undertaken by maximizing the discretion possessed by law enforcement officials who handles children with problems with the law. The concept of restorative justice should be carried out with an understanding of the victim, the perpetrator, the victim's family and the family of the perpetrator and the community to work together to determine appropriate action against the medical rehabilitation of drug abusers of children. Keywords: Punishment, the Child Abuse To Narcotics and Law Progressive